Unions and Equity. - O`Shaughnessy, T (Department of Economics (University of Oxford), 2000)
Trade unions have been successful in compressing the wage distribution but not in influencing the share of national income going to labour. This paper claims that a compressed wage distribution provides insurance in the same way that the tax and benefit system does and thus may be welfare-improving. Moreover, a union-based wage compression system may be a better than a conventional taxbenefit system in providing such insurance and may well complement the operation of the latter. Models of wage compression and of taxes and benefits are evaluated and then combined in a single model. The wage compression system works well for the least skilled but the tax-benefit approach is better if average utility is being maximized. In the combined model the two mechanisms complement one another. Equityefficiency trade-offs in the combined system mostly dominate those obtained from each mechanism acting on its own. A key factor is the willingness of skilled workers to ”defect” from a wage compression agreement. Encouraging ”defection” may appeal to policy-makers (labour markets are more ”flexible”) but the benefits of a compressed wage distribution may be lost, placing stress on welfare state institutions and undermining the insurance function that the combined wage-compression/tax-benefit system delivers relatively efficiently.